Moonlight over Paris : a novel - Robson, Jennifer, 1970- (William Morrow, an imprint of HarperCollinsPublishers, 2016)
"Spring, 1924. Recovering from a broken wartime engagement and a serious illness that left her near death, Lady Helena Montagu-Douglas-Parr vows that for once she will live life on her own terms. Breaking free from the stifling social constraints of the aristocratic society in which she was raised, she travels to France to stay with her free-spirited aunt. For one year, she will simply be Miss Parr. She will explore the picturesque streets of Paris, meet people who know nothing of her past, and pursue her dream of becoming an artist ... [She soon meets] Sam Howard, an irascible and infuriatingly honest correspondent for the Chicago Tribune"--Cover flap.